Sensitivity Test of Staphylococcus Aureus and Staphylococcus Epidermidis in Women Taking Routine Beauty Care of Clinics to Various Antibiotics - Yusianti Sliviani; Ardy Prian Nirwana (Indonesian Journal of Global Health Research, 2022)
Acne is a skin problem that is often experienced by teenagers. Acne treatment is mostly taken in beauty clinics. One of the causes of acne is bacteria, namely Staphylococcus aureus and Staphylococcus epidermidis. The use of antibiotics is often given by beauty clinics to treat acne problems. The irrational use of antibiotics and in a long term as well as within improper dose can cause resistance to bacteria. The purpose of this study is to determine the sensitivity of Staphylococcus aureus and Staphylococcus epidermidis to various antibiotics. The research was conducted in Bacteriology Laboratory of STIKES Nasional from January – December 2021.The study was conducted descriptively from January to December 2021. The population taken by quota sampling in this study was women having treatment at beauty clinics. The sensibility test was carried out by using the Kirby Bower method. S. aureus and S. epidermidis were found in 8 samples from 20 samples examined. Sensibility test showed 25% of S. aureus was sensitive to clindamycin 75% sensitive to Penicilin, 75% sensitive to Tetraciklin, 50% sensitive to Eritromicin, 75% sensitive to Cefoxitin, 100% sensitive to Ciproflosaxin and Gentamicin. Whilst 100% of S. epidermidis was resistant to clindamycin and erythromycin, 100% sensitive to Penicilin, Tetraciklin, Cefoxitin, Ciproflosaxin, Gentamicin. The conclusion of this study is that S. epidermidis has been resistant to erythromycin and clindamycin, whilst the highest resistance of S. aureus is to clindamycin.